Caracterização e análise do estado mental e funcional de idosos institucionalizados em instituições públicas de longa permanência - Converso, Maria Estelita Rojas [UNESP]; Iartelli, Isabele [UNESP] (FapUNIFESP (SciELO), 2007)
Background: This study had as objective to characterize the institutionalized elderly residents in three long-term care facilities, about their functional capacity and mental state, and to evaluate if there is a correlation between both. Methods: To do so, three instruments were used: an identification form, the Mini-Mental State Examination (MMSE) and Barthel's Index. For statistical analysis the Person's Correlation and ANOVA Test were used. Results: The population studied consisted of 115 elders with ages between 62 and 104 years old, 40.66% females and 59.13% males. 49.56% are literate and 50.43% illiterate. Regarding the marital status, singles (46.65%) and widows (21.8%) were predominant. About the mental and functional state, there was a high rate of elders showing cognitive decline (76.72%) and functionally independent (75.65%). Conclusions: According to the results, one can notice that there is a mild degree of correlation between the Barthel's Index and MMSE (r = 0.441; p < 0.000), and the variables of gender and age are not influenced in the results of these instruments. There is a significant statistical relation (p < 0.0001) between education and mental and/or functional state of the individual.
Analysis and characterization of functional capacity and mental state in residents in old folk's home
Keywords: Dementia; Elderly; MMSE; adult; aged; analysis of variance; cognitive defect; controlled study; elderly care; female; functional status; human; human experiment; male; mental health; mini mental state examination; sex difference